Modern approaches to background monitoring of soil cover by space scanning data - Byndych Т. Yu.; Plisko, I. V.; Sherstyuk, A. I.; Romanchuk, K. Yu. (AgroChemistry and Soil Science, 2023)
The purpose of the article is to describe a practical methodology for thematic processing of satellite imagery data of virgin land as a basis for creating a modern system of information support for background monitoring of soils. The methodical approach developed based on archival data of the Landsat 8 satellite. The testing of methodological developed approaches for background monitoring performed on the example of the soil studies of the Mykhailivska virgin land, which is the only preserved area of virgin meadow steppe in the Forest-Steppe zone of Ukraine. The research included statistical analysis and processing of different time space images of the virgin area, in particular, the calculation of the vegetation index NDVI and the numerical taxonomy of its quantitative values by cluster analysis (ISODATA method); analysis of archival data of the field survey of this territory; geostatistical analysis of spatial variation of soil indicators. Тhe use of vegetation indices obtained by multi temporal satellite images introduced as indirect indicators to the integral change assessment of soil quality and state of soil cover. Comparative analysis of the results of decoding of different-time space images of the Mykhailivska virgin land carried out by the information model, which based on the probabilistic formalization of territorial division and described by calculating several information indicators of complexity. The analysis of these indicators show a decrease in the complexity of the spatial structure of the distribution of vegetation in the period from 2014 to 2019 years. The verification of developed approach carried out by means of selective determination of soil penetration resistant. The results of the dispersion analysis showed that the "vegetation" contours determined based on the vegetation index NDVI are significantly different in terms of soil penetration resistant values.